The Mfge8‐α8β1;1‐PTEN pathway regulates airway smooth muscle contraction in allergic inflammation. Issue 11 (15th May 2018) - Khalifeh-Soltani, Amin; Gupta, Deepti; Ha, Arnold; Podolsky, Michael J.; Datta, Ritwik; Atabai, Kamran
ABSTRACT: Asthma affects ~300 million people worldwide. Despite multiple treatment options, asthma treatment remains unsatisfactory in a subset of patients. Airway obstruction is a hallmark of allergic asthma and is largely due to airway smooth muscle hypercontractility induced by airway inflammation. Identification of molecular pathways that regulate airway smooth muscle hypercontractility is of considerable therapeutic interest. We previously identified roles for milk fat globule epidermal growth factor–like 8 (Mfge8) in opposing the effects of allergic inflammation on increasing airway smooth muscle contractile force. In this study, we delineate the signaling pathway by which Mfge8 mediates these effects. By using genetic and pharmacologic approaches, we show that the α8β1 integrin and the phosphatase and tensin homolog (PTEN) mediate the effects of Mfge8 on preventing IL‐13–induced increases in airway contractility. Tracheal rings from mice with smooth muscle–specific deletion of α8β1 or PTEN have enhanced contraction in response to treatment with IL‐13. Enhanced IL‐13–induced tracheal ring contraction in Mfge8 ‐/‐ mice was abolished by treatment with the PI3K inhibitor. Mechanistically, IL‐13 induces ubiquitination and degradation of PTEN protein. Our findings identify a role for the Mfge8–α8β1–PTEN pathway in regulating the force of airway smooth muscle contraction in the setting of allergic inflammation.—Khalifeh‐Soltani, A., Gupta, D., Ha, A., Podolsky, M. J., Datta, R., Atabai, K. The Mfge8‐α8β1‐PTEN pathway regulates airway smooth muscle contraction in allergic inflammation. FASEB J. 32, 5927–5936 (2018). www.fasebj.org